Deglacial patterns of South Pacific overturning inferred from 231Pa and 230Th - Ronge, Thomas; Lippold, Jörg; Geibert, Walter; Jaccard, Samuel L.; Mieruch-Schnülle, Sebastian; Süfke, Finn; Tiedemann, Ralf (Scientific reports, 2021)
The millennial-scale variability of the Atlantic Meridional Overturning Circulation (AMOC) is well documented for the last glacial termination and beyond. Despite its importance for the climate system, the evolution of the South Pacific overturning circulation (SPOC) is by far less well understood. A recently published study highlights the potential applicability of the 231Pa/230Th-proxy in the Pacific. Here, we present five sedimentary down-core profiles of 231Pa/230Th-ratios measured on a depth transect from the Pacific sector of the Southern Ocean to test this hypothesis using downcore records. Our data are consistent with an increase in SPOC as early as 20 ka that peaked during Heinrich Stadial 1. The timing indicates that the SPOC did not simply react to AMOC changes via the bipolar seesaw but were triggered via Southern Hemisphere processes.
Im Text sind "231" und "230 "hochgestellt
Gesehen am 24.12.2021